Hybrid Flow Bioreactor with All Catalysts Immobilized for Enzymatic Electrosynthesis. Issue 16 (28th July 2022) - El Housseini, Wassim; Lapicque, François; Pontvianne, Steve; Vilà, Neus; Mazurenko, Ievgen; Walcarius, Alain; Etienne, Mathieu
Abstract: The electrochemical regeneration of the reduced form of nicotinamide adenine dinucleotide cofactor (NADH) was realized in a hybrid flow reactor coupling fuel cell technology and redox flow device, paying attention to the robust immobilization of all catalysts. The rhodium catalyst Rh(Cp✶)(bpy)Cl + was covalently immobilized on a multi‐walled carbon nanotube (MWCNT) layer and the association with the gas diffusion electrode was carefully optimized. High stability and activity of the electrochemical system were assessed by cyclic voltammetry and amperometry in the flow reactor. Afterwards, the optimal cofactor regeneration was applied to NADH‐dependent biosynthesis using immobilized lactate dehydrogenase for the conversion of pyruvate to lactate in the flow cell in the presence of cofactor concentration as low as 10 μM. 79 % Faradaic efficiency was achieved and remarkable total turnover number (TTN) were reached: 2500, 18000, and 180000, for NADH, Rh complex and L‐lactate dehydrogenase (LDH), respectively. Abstract : Immobilizing all catalysts : High total turnover of NADH cofactor can be achieved with using all‐immobilized catalysts in a hybrid flow bioreactor allowing efficient transfer of electrons and protons from H2 reacting in a gas diffusion electrode to the enzymatic reaction with only 10 μM enzymatic cofactor.β‐nicotinamide adenine dinucleotidebioconversionelectrochemical regenerationgas diffusion electroderedox flow